The Impact of Tourism on Village Society - Festivalia, Filma; Enggriani, Mimi; Pramanik, Purwanti Dyah (Institut Pariwisata Trisakti, 2019)
The research aimed to analyze “The Impact of Tourism on Village Society”. The methodology of the study was quantitative research and descriptive analysis. The research was located in Sumurugul village. Respondents of this research were 92 residents. The data was collected by using convenience sampling. The data was analyzed by using validity and reliability test, frequency, and descriptive (mean) analysis. The study found that there is the positive impact of tourism on village society in Sumurugul in the point of economics, social, and environment aspect. The implication of this study showed that tourism should be one of the alternatives to develop a village.